Understanding Diversity: Antidiscrimination Education and Intercultural Education - Katarzyna Smoter (Vasyl Stefanyk Precarpathian National University, 2018)
The issue of social exclusion and the consequences of this process for members of minority groups is becoming increasingly important in the field of education. The answers to this state are the postulates of anti-discrimination education and intercultural education. It is worth reflecting what common features, and what are the differences between the two approaches? How can we define the interrelationships between the intercultural education and anti-discrimination education? In this article the two approaches are mentioned as: "the two sides of the same coin" and also as: "anti-discrimination education as a specific continuation of intercultural education ... and vice versa", or as a result of seeing different problems "being together in manifold world". These different reviews of the problem generate different consequences for understanding these two approaches. Their association may be present in a variety of events and initiatives at both school and other institutions of education and socialization among children, adolescents and adults.